Design and Simulation Analysis of Hexapod Bionic Spider Robot. Issue 2 (February 2019) - Sun, Chao; Yuan, Minghai; Li, Fan; Yang, Zihao; Ding, Xianyou
Abstract: According to the study of the physiological structure characteristics of hexapod insects, this paper proposes a design scheme of a hexapod bionic spider robot. According to the flexibility and stability requirements of the hexapod bionic spider robot, the body of the spiderlike robot is designed from the perspective of bionics. The original model is further optimized by analyzing the structural proportion of the robot's legs and the defects of the original design. Finally, the static analysis of the hip and knee joints of the robot is carried out to verify the rationality of the hexapod bionic spider robot mechanism.